(untitled) (Research, Society and Development, 2023)
The objective of this review is to demonstrate essential aspects of the female prostate, adding historical and scientific literature, and contextualizing current reports on the development, morphological, pathological aspects and biological functions that this gland may present. The present study is a narrative review of research on the female prostate. A search for articles was carried out in the Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Library Online (SciELO) and PubMed databases, with the following Health Sciences Descriptors (DeCS): Female ;Female Gland; Prostate Gland; prostate. Articles were selected between the periods of 1880 to 2023, in German, Spanish, English and Portuguese. Contrary to popular belief, the prostate is not a gland found only in male humans. Research shows that this gland is present in several mammals, including female humans. The hormonal environment is altered by the action of several endocrine disruptors and through these factors, malignant tumors can occur in their structure, as they occur in males. It is noticeable the range of pathologies that have the potential to affect the female prostate, diseases present in cases already reported in the literature. It is necessary to improve observational and literary studies about the female prostate, for the detailed clarification of the biological and evolutionary functions of this gland. In addition to epidemiological research on the pathologies that can affect the female public, because, even in rare cases, they can be obstacles to human health in the future. in asepsis or in basic safety concepts.